Sepsis diagnosis and monitoring – procalcitonin as standard, but what next? (Anestezjologia Intensywna Terapia, 2019)
Sepsis is a life-threatening organ dysfunction caused by a systemic altered host response to infection. According to the newest guidelines the sepsis treatment should be personalized and based on an approach specified by use of biomarkers to tailor therapy to each patient’s needs. The main features of such biomarkers should be high specificity, sensitivity and ability to monitor the progress of sepsis. There is limited application of procalcitonin (PCT), C-reactive protein (CRP) and interleukin-6 (IL-6) for reaching this target, because of their secretion during non-infectious processes. The purpose of this review was to introduce four biomarkers, i.e. kallistatin, testican-1, presepsin and mid-regional pro-adrenomedullin, and compare their usefulness in diagnosing sepsis with PCT, CRP and IL-6.